The Cinematic Canvas of Politics: A Framing Analysis of Dirty Vote Film During the 2024 Election Cycle - Dede Mercy Rolando; Tantan Hermansah; Rahmah Ningsih (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research discusses the documentary film